(untitled) (Journal of Engineering, 2003)
r three-phase converters, the knowledge of the orders and relative amplitudes of lower harmonic components is essential for a filter design. Under unbalanced conditions of the supply voltage, harmonics that are not produced under balanced conditions are generated. The effect of unbalanced- supply conditions on the harmonics generated in the primary of a Transformer feeding a three- phase six- pulse uncontrolled converter is investigated theorticaly .The validity of theortical results is demonstrated practically.